Predicting Entrepreneurial Intentions and Improve of Life Cycle among Asnaf Gen Z - Siti Nor Bayaah Ahmad; Ikmal Malik (Human Resource Management Academic Research Society (HRMARS), 2023)
Purpose: This study examine the impact of specific entrepreneurial characteristics on the entrepreneurial attitudes of Malaysia's Asnaf generation Z. Extended theory of planned behaviour was used to examine how factors such as innovation, life style, behavioural control, life cycle, need for achievement and resources, attitude toward entrepreneurship and subjective norms and behavioural control had influenced the entrepreneurship intention and Gen Z's expectation towards changing the life cycle. Design/methodology/approach: 106 university students from Sabah and Selangor took part in the study's quantitative data gathering using an online survey. For the purposes of data analysis, PLS-SEM, or partial least squares structural equation modelling, was employed. Findings: The results revealed that attitudes toward entrepreneurship, subjective norms, and perceived behavioural control had an indirect impact (entrepreneurial intention) on respondents' behaviour in order to improve their life cycle. In terms of entrepreneurial intent, several of the antecedents appeared to have a substantial and insignificant relationship. When it came to entrepreneurial ambition, the antecedents of need for accomplishment and lifestyle were both found to have a P value greater than 0.005. Research limitations/implications: This study focuses on the idea of an entrepreneurial on Asnaf student and attempts to integrate the elements indicated in the past literature on entrepreneurship with the opinions of subject-matter experts. Practical implications: It is recommended that kids should be taught about entrepreneurship from an early age, and that universities should place a particular priority on teaching entrepreneurial skills to low-income students. Learning entrepreneurial skills can equip the younger generation with practical and valuable skills that can help them find employment, be more adaptable to job markets and able to create their own opportunities for success. Originality/value: This study looked into the elements that influence Asnaf generation Z's interest in entrepreneurship, as well as how their entrepreneurial intentions influence young people's behaviour in terms of enhancing their life cycle. The researchers are hoping that these younger generations will be able to establish a better life for themselves than their parents currently have.